Asma na mulher - Vale, Simone Alves do [UNESP]; Coelho, Liana Sousa [UNESP]; Minamoto, Suzana Erico Tanni [UNESP]; Godoy, Irma de [UNESP] (My University, 2013)
Asthma is a chronic inflammatory disease of high prevalence and high morbidity if left untreated. Some differences are noted between men and women, particularly in disease manifestation, but diagnosis and treatment did not differ between genders. Some peculiarities of asthma in women will be discussed in this review, as well as the treatment of pregnant women with asthma. © Copyright Moreira Jr. Editora.

A asma é doença inflamatória crônica de alta prevalência e com alta morbidade se não tratada. Algumas diferenças são notadas entre homens e mulheres, principalmente na manifestação da doença, porém diagnóstico e tratamento não diferem entre os gêneros. Algumas peculiaridades da asma na mulher serão discutidas nesta revisão, bem como o tratamento da gestante asmática.
Asthma in woman
Keywords: Asthma; Pulmonar inflammatory disease; Asma; Doença inflamatória pulmonar